PELATIHAN KEAHLIAN DAN PENERAPAN TEKNOLOGI IT BERPENGARUH TERHADAP KINERJA KARYAWAN PT. TELKOM INDONESIA,Tbk UNIT GES WITEL DENPASAR - Wiryawan Suputra Gumi; Ni Putu Chandra Adnyani (Forum Manajemen STIMI Handayani Denpasar, 2022)
Professional human resource management is one of the important aspects in the company. There are several indicators that can affect human resources, namely training, development, performance, and job satisfaction. Not only human resource management, one of the factors that can affect the internal and external success of a business or business and increase productivity and employee performance is the existence of information technology. The purpose of this study was to analyze the effect of skills training on employee performance, to analyze the effect of IT technology on employee performance and to analyze IT skills and technology training on employee performance at PT. Telkom Indonesia, Tbk Unit GES Witel Denpasar. The types of data used in this study are qualitative and quantitative data, with the data source being primary data. The data collection method was carried out by distributing questionnaires to the respondents, while the data analysis techniques used were: classical assumption test and hypothesis testing. The results showed that IT skills and technology training had a significant effect on employee performance at PT. Telkom Indonesia, Tbk Unit GES Witel Denpasar.